SAT0015 Anca-associated vasculitis- and systemic lupus erythematosus-induced neutrophil extracellular traps have intrinsically different features. (15th June 2017) - Dam, LS Van; Kraaij, T; Kamerling, SW; Avramut, MC; Jost, CR; Koster, AJ; Scherer, HU; Pusey, CD; Rabelink, AJ; Kooten, C van; Teng, YK
Abstract : Background: Neutrophil extracellular traps (NETs) are immunogenic, extracellular DNA structures that harness important autoantigens to be recognized by the adaptive immune system. NETs are thought to play a pivotal role in the pathogenesis of many systemic autoimmune diseases including ANCA-associated vasculitis (AAV) and systemic lupus erytematosus (SLE). However it is still unclear how and if NETs can act as a common pathway in the pathophysiology of these clinically divergent autoimmune diseases. Objectives: To investigate the characteristics of NETs induced by sera of AAV and SLE patients. Methods: The present study involved 101 AAV patients, 59 SLE patients and 10 healthy controls. Healthy neutrophils were stimulated with 10% serum of these patients to induce NETs. Quantity of NET induction was measured by a novel, highly-sensitive NET quantification assay using 3D-confocal laser scanning microscopy 1 . Qualitative characteristics of NETs were investigated by immunofluorescence microscopy that detected co-localisation of several established autoantigens and NET-markers on AAV- and SLE-induced NETs, including citrullinated histon-3 (CitH3), neutrophil elastase (NE), high mobility group box-1 (HMGB1), myeloperoxidase (MPO) and proteinase-3 (PR3). Additionally, the morphology and kinetics of AAV- and SLE-induced NETosis were visualized by live imaging and electron microscopy. Results: Quantifying ex vivo NET induction demonstrated that AAV sera induced significant more NETs (median [Q1 - Q3]: 20.74 [9.56 – 74.14]), compared to SLE sera (5.02 [1.88 – 14.33]). Also qualitatively, NETs induced by AAV or SLE sera were distinct. In both cases, NETs showed co-localisation of MPO and PR3 with extracellular DNA. However, AAV-induced NETs had significantly higher Cith3 expression than SLE-induced NETs. Interestingly, the opposite was observed for other markers as HMGB1 was exclusively expressed on SLE-induced NETs and NE was also higher expressed on SLE-induced NETs compared to AAV-induced NETs. Intriguingly, the distinction between AAV and SLE NETs was further corroborated by live imaging demonstrating differences in morphology and chronology of NET induction: in SLE NET-clusters were induced within the 1st hour while in AAV non-clustered NETs composed of long, thin DNA-fibres were induced in 2–4 hours through lytic expulsion. Conclusions: The present study demonstrates that NET induction in AAV and SLE results in quantitative and qualitative distinct NETs indicating that NET formation in AAV and SLE is likely based on intrinsically different processes. These data increase our understanding of the pathophysiologic relevance of NETs and how they could be considered as a common pathway underpinning different autoimmune diseases. References: Kraaij T, et al, A novel method for high-throughput detection and quantification of neutrophil extracellular traps reveals ROS-independent NET release with immune complexes, Autoimmun Rev (2016). Disclosure of Interest: None declared